2013
DOI: 10.1002/cbm.1880
|View full text |Cite
|
Sign up to set email alerts
|

Service attachment: The relative contributions of ward climate perceptions and attachment anxiety and avoidance in male inpatients with psychosis

Abstract: Background It has been suggested that mental health services can help meet the attachment needs of inpatients and improve patient outcomes through the provision of a ‘secure base’; however, what defines the latter is unclear. Perception of ward climate might be a useful indicator. Aim The aim of this study was to examine whether inpatient perceptions of the ward climate, which is partly under the control of the service, or inpatients' own personal levels of attachment anxiety and avoidance are more associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(172 reference statements)
0
4
1
Order By: Relevance
“…This result differs from results found in previous research where age was not found to be related to the perception of ward climate (Campbell et al, 2014;Middelboe et al, 2001;Pedersen and Karterud, 2007). In our study there was a positive relationship between age and therapeutic hold.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result differs from results found in previous research where age was not found to be related to the perception of ward climate (Campbell et al, 2014;Middelboe et al, 2001;Pedersen and Karterud, 2007). In our study there was a positive relationship between age and therapeutic hold.…”
Section: Discussioncontrasting
confidence: 99%
“…The aim of this current study is to provide more insight into the relationship between patient characteristics and perceived ward climate. Based on previous findings, the demographic characteristics that might be related to perception of ward climate targeted in the present study were patients' age (Campbell, Allan, & Sims, 2014;Middelboe et al, 2001;Pedersen & Karterud, 2007), length of stay within the facility (van der Helm et al, 2014), and risk of violence (Dickens et al, 2014). With respect to pathological personality features, there are reports that psychopathy may be a key determinant of climate in forensic therapeutic settings (Harkins, Beech, & Thornton, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…The role of attachment in psychosis is relevant to wider considerations of the social world of those experiencing psychosis, where symptoms, internalized self‐stigma and negative self‐concepts can impair the ability to relate (Brabban et al, 2017; Lim et al, 2018). Research considering attachment and psychosis has begun to inform work in various settings, including inpatient wards (Campbell et al, 2014). There is also growing research into the benefits of affirmative spaces such as the charity The Hearing Voices Network that report similar themes regarding the freedom to be oneself, connect with others and make sense of one's experiences (Payne et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant correlations have been observed between the EssenCES and other measures of milieu, ward atmosphere, relational security, and the treatment/ working environment of secure settings (Day et al, 2011;Livingston, Nijdam-Jones, & Brink, 2012;Schalast & Groenewald, 2009;Schalast et al, 2008;Tighe & Gudjonsson, 2012;Tonkin et al, 2012). Furthermore, significant relationships have been observed between the EssenCES and measures of resident satisfaction with treatment services (Bressington et al, 2011;Campbell, Allan, & Sims, 2014). Also, significant relationships have been observed between the EssenCES and readiness to engage in therapeutic interventions, the number of treatment sessions attended, the perceived strength of the resident-therapist relationship, and the number of seclusions, aggressive, and security incidents engaged in (Day et al, 2011;Long, Anagnostakis et al, 2011;Tonkin et al, 2012).…”
Section: Cies/wasmentioning
confidence: 98%